2018
DOI: 10.1186/s12967-018-1643-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgical peritoneal stress creates a pro-metastatic niche promoting resistance to apoptosis via IL-8

Abstract: BackgroundThe mainstay of treatment of advanced ovarian cancer (AOC) involves chemotherapy, and debulking surgery. However, despite optimal surgical procedure and adjuvant chemotherapy, 60% of patients with AOC will relapse within 5 years. Most recurrences occur in the peritoneal cavity, suggesting the existence of occult sanctuaries where ovarian cancer cells (OCC) are protected. In murine models, surgical stress favors tumor growth; however, it has never been established that surgery may affect OCC sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…A plausible albeit speculative explanation relates to the violent inflammatory response caused by ultra-radical surgery that potentially abates the positive effects of complete resection. Studies suggest that surgical stress and trauma promotes a pro-metastatic environment with increased level of systemic inflammation and resistance to chemotherapy [29,30]. Clearly, our results do not corroborate previous reports on improved survival when adding ultra-radical procedures; indicating that the dogma of complete resection regardless of tumor extension is not generally applicable.…”
Section: Discussioncontrasting
confidence: 97%
“…A plausible albeit speculative explanation relates to the violent inflammatory response caused by ultra-radical surgery that potentially abates the positive effects of complete resection. Studies suggest that surgical stress and trauma promotes a pro-metastatic environment with increased level of systemic inflammation and resistance to chemotherapy [29,30]. Clearly, our results do not corroborate previous reports on improved survival when adding ultra-radical procedures; indicating that the dogma of complete resection regardless of tumor extension is not generally applicable.…”
Section: Discussioncontrasting
confidence: 97%
“…By means of intravital microscopy in tumors, previous studies observed that neutrophils present directional motility to the tumor and the formation of DNA NETs (personal communication). In the tumor context, these structures have been associated mainly with processes that favor metastasis [6668]. An intravascular role of neutrophils is proposed, whose DNA favors the persistence and survival of tumor cells in the bloodstream [69, 70].…”
Section: Polymorphonuclear Leukocytes and Net Production In Tumor mentioning
confidence: 99%
“…CSCs play a vital role in regulating TME which is important to maintain the malignant proliferation [79][80][81][82]. However, interleukin from TME could prime a positive feedback loop which is important in stressing the stemness of tumor [83][84][85].…”
Section: Discussionmentioning
confidence: 99%